Rupturing cancer cells by the expansion of functionalized stimuli-responsive hydrogels - Fang, Yan (2018)
Using particles with different functionalities for treating cancer has many advantages over other methods (for example, better access to remote parts of the body); however, current chemical (for example, chemotherapy) and biological (for example, immunotherapy) methods still face many challenges. Here, we describe a fundamentally different approach: using the physical force of an expanding stimuli-responsive hydrogel to rupture cancer cells attached on its surface. Specifically, we coated temperature-responsive hydrogels with a layer of cell-adherent arginine-glycine-aspartate (RGD) peptides. The approach involved first allowing cancer cells to attach onto the surface of the hydrogels, and then applying a change in temperature. As the hydrogel underwent a chemical transformation and expanded due to the stimulus, the cancer cells attached to it ruptured. The results from staining the cells with trypan blue, observing them using SEM, and analyzing them using the MTT assay showed that both breast and lung cancer cells died after the hydrogel expanded; hence, we showed that this physical force from the expanding hydrogel is strong enough to rupture the cancer cells. In addition, the force derived from the expanding hydrogel was determined separately to be larger than that needed to rupture typical cells. This physical approach is conceptually simple, technically easy to implement, and potentially generalizable for rupturing a wide range of cells.